The Egyptology handbook : a course in the wonders of Egypt - Sands, Emily (Cambridge, MA : Candlewick Press, 2005)
The story of Emily Sands's ill-fated expedition to find the lost tomb of Osiris was told in her journal, Egyptology. Now a new book, written by Miss Sands for her neice and nephew, has been discovered. Here, in this illustrated course book, Sands offers thirty lessons exploring the history and culture of Ancient Egypt that are sure to make you an undeniable expert in Egyptology!
Ages 9-12
Keywords: Egypt -- Civilization -- To 332 B.C. -- Juvenile literature